Scale of emotional development–short: Reliability and validity in two samples of children with an intellectual disability. (January 2021) - Sterkenburg, P.S.; Kempelmann, G.E.M.; Hentrich, J.; Vonk, J.; Zaal, S.; Erlewein, R.; Hudson, M.
Highlights: Psychometric assessment of the SED-S in children with intellectual disability (ID). SED-S was found to be a coherent tool to assess emotional development. SED-S is a valid scale for assessing emotional functioning in children with ID. SED-S was found to be a reliable and valid instrument. Divergent validity is indicated in relation to ASD and visual impairment. Abstract: Background: Intellectual disability (ID) is often accompanied by more significant delays in emotional development than in cognitive development. Diagnostic assessment can provide insight into emotional functioning. However, few standardized assessment instruments are available. Aims: Examine the reliability and validity of the Scale of Emotional Development–Short (SED-S) in children with ID. Methods and procedures: This methodological instrument validation study was conducted in the Netherlands and Switzerland with children ( N = 118) older than 3 and younger than 18 years with ID ranging from profound to mild. Measures included: demographic and medical data, SED-S, and the Vineland. Coherence and reliability of the SED-S were determined using Cronbach's alpha, and validity was examined using Goodman and Kruskal's γ, Kruskal-Wallis H, and Mann-Whitney U tests. Outcomes and results: The reliability of the SED-S was high, the convergent validity was good, and divergent validity was indicated in relation to autism spectrum disorder (ASD), visual and/or auditory impairment, and adaptive functioning. Further research: Research is needed to better understand the implications of ASD and visual and/or auditory impairment on emotional development and their association with (normal) intelligence. Children with ID may also benefit from (more) detailed guidelines for imbalanced profiles on the SED-S.